New Internet Resources аs а Tоol fоr Tеаching а Nоn-Nаtivе Lаnguаgе - S.А.Аdilоvа (Genius Journals, 2022)
The article deals with such relatively new Internet resources as Web 2.0 technologies. The author provides a definition of such resources, types and ways of their use when teaching a non-native language in higher educational institutions.
Keywords: Applied Linguistics; Language Teaching Methods; Wеb 2.0 Tеchnоlоgiеs; Multimеdiа